(untitled) (Annals of Medical Research, 2023)
Aim: Rosacea is a chronic inflammatory dermatological disease characterized with erythema, telangiectasias, papules and pustules that is seen more frequently in individuals with fair skin. Our purpose in this study is to compare choroidal measurements of rosacea patients with healthy individuals. Materials and Methods: Right eyes of 30 patients with ocular rosacea and right eyes of 30 healthy participants matched in terms of age and sex were included in the study. Choroid thicknesses were measured manually using optical coherent tomography device from the central subfovea; from the temporal as 1000 µm horizontally from the fovea and from the nasal. Results:Subfoveal, temporal and nasal choroidal thicknesses were measured as 351.90 µm±103, 335.10±100 µm, 322.00±99 µm, respectively in the ocular rosacea group; as 323.50±61 µm, 311.95±63, 302.35±61 µm, respectively in the control group. However, all these differences were not found to be statistically significant (p>0.05). Conclusion: Though many vascular disorders are observed in ocular rosacea, choroidal thickness is not affected by them. New studies including more patients with a longer period of follow-up are needed in this field.